2015
DOI: 10.3109/0284186x.2015.1088171
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive longitudinal overview of health-related quality of life and symptoms after treatment for rectal cancer in the TME trial

Abstract: Background: Total mesorectal excision (TME) combined with preoperative short-term radiotherapy (PRT) reduces local recurrence rates in rectal cancer treatment. However, treatment with radiotherapy increased morbidity and did not result in a longer survival. The aim of this analysis is to provide a comprehensive longitudinal overview of the health-related quality of life (HRQL) and symptoms experienced by rectal cancer patients in the Dutch randomized TME trial from baseline until 14 years after treatment. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…204 Patients in the Dutch TME-trial that received RT reported impaired quality of life (QoL) even after a follow up of 14 years. 205 However, no impact on general symptoms was seen in the irradiated group. Symptoms of urinary dysfunction such as increased frequency, chronic cystitis and incontinence are more common in patients after RT.…”
Section: Toxicity From Radiotherapymentioning
confidence: 85%
“…204 Patients in the Dutch TME-trial that received RT reported impaired quality of life (QoL) even after a follow up of 14 years. 205 However, no impact on general symptoms was seen in the irradiated group. Symptoms of urinary dysfunction such as increased frequency, chronic cystitis and incontinence are more common in patients after RT.…”
Section: Toxicity From Radiotherapymentioning
confidence: 85%
“…However, other studies have shown that AF and HRQOL seem to stabilize 1 to 2 years after treatment and deteriorate slowly thereafter. 26 Third, baseline scores were obtained when the patients already had a tumor in the rectum. The impact of the tumor on anorectal function and some domains of HRQOL is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] However, treatment of intermediate-and high-risk rectal cancer, involving neoadjuvant radiotherapy with or without chemotherapy followed by total mesorectal excision (TME), is invasive and associated with significant postoperative short-and long-term morbidity. [4][5][6] As more patients live with the consequences of treatment, resulting from both the increasing rectal cancer incidence and the improving survival rate, 7 patients' quality of life (QOL) has increasingly become a focus of attention.…”
Section: Introductionmentioning
confidence: 99%